Emerging trends in biomass-derived porous carbon materials for energy storage application: A critical review. (March 2023) - Priya, D. Siva; Kennedy, L. John; Anand, G. Theophil
Abstract: Developing a clean and novel energy storage system is the need of the hour due to the immediate consumption of fossil fuels and the escalation of environmental concerns. The biomass-derived porous carbon materials in energy storage applications have attracted much interest among researchers due to their environmentally friendly, natural abundance, ease of fabrication, cost-effectiveness, and sustainability of the macro/meso/microporous carbon produced from various biological precursors. In this review, the development and components of supercapacitor energy storage device was described in detail. This paper reviews biomasses exhibiting high surface area achieved from 215 to 3532 m 2 /g and porous carbon electrodes exhibiting specific capacitance from 44 to 1050 F/g and performance around 99.7% capacitive retention over 1000 cycles and from the lowest 5.1 Wh/kg to high energy density of 138.4 Wh/kg exhibited by symmetric supercapacitor were discussed. This review presents a comprehensive analysis of the impact of the biomass elemental compositions requirements on the porous carbon yield. It also highlights and analyzed various structured porous carbon materials on the electrochemical performance. This review is expected to inspire future emerging research trends and challenges in synthesizing porous carbon from biomass precursors for energy storage applications.